Investigating Student’s Acceptance of an EDMODO Content Management System - Zain, Farah Mohamad; Hanafi, Effariza; Don, Yahya; Yaakob, Mohd Faiz Mohd; Sailin, Siti Nazuar (Eskisehir Osmangazi University, 2019)
The aim of this study is to examine the factors that influenced the use of Edmodo content management system to support the teaching and learning in a flipped classroom context. Using an extended technology acceptance model (TAM), we adopted a revised model consisting of two external factors (Content Quality and Motivation) that may influence students' perceptions and acceptance of the system. A total of 42 students were involved in this study. The students attended a course in a flipped classroom environment. The findings of the study utilizing the multiple regression analysis revealed that the Edmodo content management system was well accepted where the Content Quality acted as a good external factor and able to predict the students Perception of Usefulness and Perception Ease of Use. As for Motivation, it was found that there was no positive relationship with the Perception of Usefulness.